Make sure you include brackets in your solution, at first look your equation made little sense.
4^(2b-3) = 8^(1-b)
(2^2)^(2b-3) = (2^3)^(1-b)
= 2^(4b-6) = 2^(3-3b)
thus
4b-6 = 3-3b
7b = 9
b = 9/7
how did you get -9/7 ??
Q: What is the value of b in the equation 4^2b-3 = 8^1-b?
My Work/Answer:
Set each sides base to 2
2^2(2b-3) = 2^3(1-b)
cancelled bases out
solved for b
my answer - 9/7
Is my work and answer correct
Thank You
2 answers
i got 9/7 the - was just to signify what it was sorry about the confusion. I should have put an equals sign